Labor market participation, unemployment and monetary policy - Alessia Campolmi; Stefano Gnocchi (Bank of Canada, 2014)
We incorporate a participation decision in a standard New Keynesian model with matching frictions and show that treating the labor force as constant leads to incorrect evaluation of alternative policies. We also show that the presence of a participation margin mitigates the Shimer critique.
Keywords: E24; E32; E52; 330; Labour markets; Business fluctuations and cycles; Transmission of monetary policy